2019
DOI: 10.1590/s0004-2803.201900000-10
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery and Binge Eating Disorder: Should Surgeons Care About It? A Literature Review of Prevalence and Assessment Tools

Abstract: BACKGROUND: Eating pathologies among bariatric surgery candidates are common and associated with adverse surgical outcomes, including weight regain and low quality of life. However, their assessment is made difficult by the great variety and inconsistent use of standardized measures. OBJECTIVE: The purpose of this review was to synthesize current knowledge on the prevalence of binge eating disorder (BED) in presurgical patients and to make a critical appraisal of assessment tools for BED. METHODS: A searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
(81 reference statements)
3
9
1
9
Order By: Relevance
“…More anecdotal, in our sample, the prevalence of BED was of 22.31%, which is consistent with the prevalence reported by the literature [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…More anecdotal, in our sample, the prevalence of BED was of 22.31%, which is consistent with the prevalence reported by the literature [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The rate of current EDs in participants planning or receiving bariatric surgery was more than double that of those who had not planned or received the surgery (33.3% compared to 14.4%) and about double that of rates of EDs in the general Australian population (17.1%) [ 9 ]. The rate of lifetime BN/BED in the present study was 41.7% (over ten times the rate in the general Australian population) and this compares with clinical population samples of bariatric surgery candidates, which ranged from 6 to 64% [ 14 , 16 , 17 , 18 , 19 ]. Similarly, the rate of current EDs was 34.4% in those who were planned/actual recipients of cosmetic surgery compared to 14.6% in those not reporting this and 17.1% in the general Australian population.…”
Section: Discussionsupporting
confidence: 62%
“…With regard to the prevalence of EDs in candidates for bariatric surgery, a 2007 systematic review found that rates of BED ranged from 6 to 64%, approximately one to ten times the rate in the general population [ 14 ]. Another review found the prevalence of BED in pre-surgical patients was 2% to 53% [ 17 ]. Research on the prevalence of other EDs is scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BED is frequent in obese people; prevalence of BED in bariatric populations ranged from 2% to 53%. [3] However, many people with BED are not obese, and a large number of obese people are not afflicted by eating disorders. [4] There is currently little research on amino acids, their metabolites and nucleotide metabolites levels in eating disorders.…”
Section: Comparison Of Plasma Nucleotide Metabolites and Amino Acids mentioning
confidence: 99%